Harvard business review on breakthrough thinking (Harvard Business School P. BostonUS, 1999)
Suggests how companies can encourage business creativity. Outlines the empathic design, a five-step process which can enable companies to identify customer needs. Emphasises the need for companies facing competition to explore innovative ideas, or evaporate. Suggests opportunities for innovation within companies, but cautions that the disciplines of diligence, persistence, and commitment must be coupled with the talent, ingenuity and knowledge of employees. Presents the interpretive approach to management as the best option for coping with today's rapidly changing and unpredictable markets.\n
Located in the Learning Resource Centre